EFEKTIVITAS MUSIKOTERAPI TERHADAP PENINGKATAN STATUS EMOSIONAL PADA REMAJA PUTRI DI SMK SEHATI - Euis Atikah; Yayuk Sri Rahayu; Marliana Rahma; Salsabila Fadilla; Anisah Fauziah (Asosiasi Dosen Muda Indonesia, 2025)
Adolescence is a developmental period characterized by significant emotional, psychological, and social changes that may affect mental well-being. Emotional instability during adolescence can lead to stress, anxiety, reduced self-confidence, and difficulties in social adjustment. Therefore, effective and accessible interventions are needed to support emotional health among adolescents. Music therapy has been recognized as a non-pharmacological approach that promotes relaxation, emotional expression, and psychological well-being. This study aimed to determine the effect of music therapy on the emotional status of adolescent girls. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. The research was conducted at SMK Sehati in February 2025 and involved 30 adolescent girls selected through random sampling. Emotional status was assessed using a structured questionnaire administered before and after the music therapy intervention. Data were analyzed using descriptive statistics, normality testing, and paired sample t-test analysis with a significance level of 0.05. The results showed that the mean emotional status score increased from 32.7 ± 2.4 before the intervention to 49.8 ± 2.6 after the intervention. The normality test indicated that the data were normally distributed. The paired sample t-test revealed a statistically significant difference between pretest and posttest scores (t = 26.842; p < 0.001), indicating that music therapy significantly improved the emotional status of adolescent girls. Participants reported feeling calmer, more relaxed, emotionally stable, and more confident after the intervention. The findings suggest that music therapy can serve as an effective, safe, and practical intervention to support adolescent emotional well-being. The originality of this study lies in its evaluation of music therapy as an emotional regulation strategy among adolescent girls within a school setting using a pretest-posttest approach. The results provide empirical evidence that may support the integration of music-based interventions into school mental health promotion programs.